Islamic financing in mitigating access to financing problems of SMEs in Malaysia: a survey analysis - Haron, Razali; Ibrahim, Khairunisah (IIUM Press, 2016)
The SMEs worldwide face the biggest problem in accessing financial assistance. By surveying selected SMEs in Malaysia, this study found similar cases as they are also facing the same problem because of a lack of collateral. Investigating the feasibility of Islamic financing schemes in providing financial aids to SMEs, this study found that several Islamic financial schemes are preferred by SMEs depending on the risk profile of SMEs. These Islamic financial schemes can build a firm liaison with SMEs in realizing the Maqasid al Shari’ah and simultaneously offer paths to better distribute wealth and prosperity among SMEs and the funders as well. This study contributes significantly to the literature as it provides insights to the nature of the SMEs and the bridge built between the SMEs and the Islamic financing schemes as to realize the Islamic social financing aim as a whole.